Mollusc fauna associated with the Cystoseira algal associations in the Gulf of Trieste (Northern Adriatic Sea) - V. PITACCO; M. ORLANDO-BONACA; B. MAVRIČ; A. POPOVIĆ; L. LIPEJ (Mediterranean Marine Science, 2014)
Mollusc assemblages associated with Cystoseira associations were sampled in the southern part of the Gulf of Trieste during the summers of 2008 and 2012. Samples were collected by SCUBA diving in the infralittoral belt (from 1 to 4 m depth). The surface within frames of 20 x 20 cm was scraped off with samples were collected by hand or with an air-lift sampler. Four erected algal species were found: Cystoseira barbata, C. compressa, C. corniculata and Halopithys incurva. A total of 69 species of molluscs were identified in those associations. Gastropoda were dominant, with the highest species richness and abundance, followed by Bivalvia and Polyplacophora. A large number of juveniles were found, proving the importance of Cystoseira associations for mollusc recruitment. Differences in composition, structure and abundance of mollusc assemblages were found for sites dominated by different algal species, and correspond to different morphology and degree of development of canopy-forming species. The present study confirms that the dominant algal species within Cystoseira associations strongly influence, although at different levels, abundance and distribution of mollusc assemblages in the Northern Adriatic Sea.